PENGARUH EDUKASI PASAR MODAL DAN LITERASI KEUANGAN TERHADAP MINAT INVESTASI GENERASI Z PADA MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS NEGERI MEDAN - Silvia Annur Hasibuan; Monika Flora Manik; Rini Khairani Harahap; Amelia; Cindi Anjuani Gultom; Khairuddin Ependi Tambunan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of capital market education and financial literacy on Generation Z investment interest among students of Economics Education, State University of Medan. The research method used is a quantitative approach with data collection techniques through questionnaires to 35 respondents. The research instrument has been tested for validity and reliability and analyzed using multiple linear regression with the help of SPSS version 25. The results of the study indicate that capital market education and financial literacy partially and simultaneously have a positive and significant effect on students' investment interest. Capital market education has a more dominant influence than financial literacy. The coefficient of determination (R²) value of 0.628 indicates that 62.8% of the variation in investment interest can be explained by these two variables, while the rest is influenced by other factors outside the study. Increasing capital market education and financial literacy is an important factor in encouraging Generation Z investment interest, especially students.